The edge of the world - Sarabande, William; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1993)
On a quest to discover the fate of his people, young shaman Cha-kwena breaks a terrifying taboo--an act that estranges him from his tribe and his woman--and follows the forbidden path of the mammoth.
Keywords: Great Lakes Region (North America) -- Fiction; Epic fiction; Historical fiction